Pengaruh Uraian Pekerjaan dan Pengawasan Terhadap Kinerja Karyawan PT. Bizgital Indonesia Jaya (BBO) Jakarta - Muhammad Ramdoni; Ananta Vidada, Irwin (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
Human resource management is a crucial component since it organizes and analyzes people to accomplish the objectives of the business or organization. All assets in the firm that including human resources as the most important component must be maximized to achieve the targeted goals. Job description and pengawasanon are the two variables examined in this study, however employee performance is the primary focus. The purpose of this study is to evaluate how PT. Bizgital Indonesia Jaya employees perform in relation to job descriptions and pengawasanon. Quantitative research using a survey strategy that blends descriptive and verification approaches is the methodology employed. Thirty employees of PT. Bizgital Indonesia Jaya made up the population in this study, and census methods were employed to use the total population as a sample. SPSS version 24 software was used to analyze the data. According to the analysis's findings, the coefficient of determination was 0,534, indicating a strong correlation between job descriptions and employee performance monitoring. In addition, the results of the coefficient of determination of 0.534 indicate that 53.4 percent of employee performance at PT. Bizgital Indonesia Jaya is influenced by job descriptions and pengawasanon.